Response to growth hormone treatment in very young patients with growth hormone deficiencies and mini-puberty - Çetinkaya, Semra; Poyrazoğlu, Şükran; Baş, Firdevs; Ercan, Oya; Yıldız, Metin; Adal, Erdal; Bereket, Abdullah; Abalı, Saygın; Aycan, Zehra; Erdeve, Senay Savaş; Berberoğlu, Merih; Şıklar, Zeynep; et al. (Walter de Gruyter Gmbh, 2018)
Background: The aim of the study was to assess the response to growth hormone (GH) treatment in very young patients with GH deficiency (GHD) through a national, multi-center study. Possible factors affecting growth response were assessed (especially mini-puberty). Methods: Medical reports of GHD patients in whom treatment was initiated between 0 and 3 years of age were retrospectively evaluated. Results: The cohort numbered 67. The diagnosis age was 12.4 +/- 8.6 months, peak GH stimulation test response (at diagnosis) as 1.0 +/- 1.4 ng/mL. The first and second years length gain was 15.0 +/- 4.3 and 10.4 +/- 3.4 cm. Weight gain had the largest effect on first year growth response; whereas weight gain and GH dose were both important factors affecting second year growth response. In the multiple pituitary hormone deficiency (MPHD) group (n = 50), first year GH response was significantly greater than in the isolated GH deficiency (IGHD) group (n = 17) (p = 0.030). In addition first year growth response of infants starting GH between 0 and 12 months of age (n = 24) was significantly greater than those who started treatment between 12 and 36 months of age (n = 43) (p <0.001). These differences were not seen in the second year. Delta Length/height standard deviation score (SDS), Delta body weight SDS, length/height SDS, weight SDS in MPHD without hypogonadism for the first year of the GH treatment were found as significantly better than MPHD with hypogonadism. Conclusions: Early onsets of GH treatment, good weight gain in the first year of the treatment and good weight gain-GH dose in the second year of the treatment are the factors that have the greatest effect on length gain in early onset GHD. The presence of the sex steroid hormones during minipubertal period influence growth pattern positively under GH treatment (closer to the normal percentage according to age and gender).
WOS: 000423677900009
PubMed ID: 29353264
Keywords: Growth Hormone Deficiency; Growth Hormone Treatment; Growth Response; Infancy; Mini Puberty